(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Breast cancer is the subsequent leading cause of cancer-related deceases among women. Initial exposure stimulates enhanced visualization and saves survives. These days, the exact grouping classification of breast cancer images is a difficult errand. There are much research works delivering various strategies and algorithms for this specific errand of medical image processing. To build up an exact characterization, this paper presents a viable classification of mammogram images utilizing HOT based classification tree and HOT based convolutional neural network (CNN). The input breast image is at first taken from the database and pre-processed by RGB to grayscale conversion and normalization methodology. In this way Histogram of Oriented Texture (HOT) Descriptor is extorted from the pre-processed images. At long last images are classified as typical or irregular utilizing HOT based classification tree and HOT based CNN. The exploratory results show that the introduced method outperforms the existing strategies concerning various performance assessments like accuracy, sensitivity, specificity, mean absolute error, AUC score, kappa statistics, and Root mean square error